Heterogeneidade ambiental explica os padrões de diversidade β taxonômica e funcional em planícies de inundação do Brasil. - Canella, Tassia Felicio (2016)
The environmental heterogeneity is a factor of great importance for diversity-β. An increase in environmental heterogeneity favors changes in the species composition and replacement of functional groups, structured by "species sorting" because more species or functional features can coexist due to a greater opportunity to be occupied niches. The abundance data and functional traits of zooplankton community, and environmental variables were used to analyze the patterns of taxonomic and functional diversity-β of microcrustaceans planktonic in dry and flooding periods in four Neotropical floodplains. It also evaluated the relationship between the taxonomic and functional diversity-β of microcrustaceans and environmental heterogeneity. The results showed that environmental heterogeneity was significantly higher in the dry season only to the Amazonian floodplain. Taxonomic diversity-β of microcrustaceans was significantly higher in the dry season in the Amazonian and Araguaia floodplain. The functional diversity-β was significantly higher in the dry to the Amazonian floodplain and filled the Araguaia and Paraná. Environmental heterogeneity significantly explained the patterns of both facets of diversity-β. It was concluded that the relationship heterogeneity-diversity-β taxonomic was more correlated in the dry season, while the functional in flooding, highlighting the importance of these relations. This positive and significant relationship indicates that deterministic processes are at work and promote an increase in facets of diversity-β, thus highlighting the importance of the mechanism "species sorting" for the planktonic community. However, it is important to highlight the role of hydrodynamics acting on diversity patterns.